2021
DOI: 10.1186/s12957-021-02331-1
|View full text |Cite
|
Sign up to set email alerts
|

Secondarily estimated cure fraction and five-year recurrence-free conditional survival probabilities among patients undergoing surgical resection for hepatocellular carcinoma presenting with minor gross vascular invasion

Abstract: Background Surgical resection (SR) has been selectively applied in hepatocellular carcinoma (HCC) presenting with minor gross vascular invasion (mGVI) which is defined when tumor invasion is confined to second-order portal branches or segmental branches of hepatic vein. However, little data of long-term outcomes are available for supporting the role of SR as a potentially curable therapeutic option for HCC presenting with mGVI. This study is aimed to estimate a statistical cure fraction and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is calculated based on the patient’s survival time and is more relevant to the actual clinical practice because it can measure the patient’s survival risk over a certain period. Conditional probability analysis is increasingly used to analyze the long-term effects of tumor characteristics [ 25 ]and is particularly suitable for comparing the difference between immediate and late-stage survival benefits after treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is calculated based on the patient’s survival time and is more relevant to the actual clinical practice because it can measure the patient’s survival risk over a certain period. Conditional probability analysis is increasingly used to analyze the long-term effects of tumor characteristics [ 25 ]and is particularly suitable for comparing the difference between immediate and late-stage survival benefits after treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Close follow-up and re-examination are needed for timely treatment to reduce mortality. Previous studies [ 26 ] had shown that approximately 7% of patients undergoing surgical treatment for HCC with mild gross vascular infiltration were expected to be cured, and conditional survival probability analysis could also be used to guide the follow-up of such patients after surgery [ 15 ]. These findings were different from our study because their research object was liver cancer patients with mild gross vascular infiltration who showed a worse prognosis than that of stage I liver cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross vascular invasion is usually a consequence of MVI progression. The poor prognosis of HCC with gross vascular invasion has been clarified, but it has a relatively large impact on the prognosis, which is not conducive to the accurate classification of the prognosis [ 35 ]. Therefore, we advocate combining CK19 and MVI to analyze the prognosis.…”
Section: Discussionmentioning
confidence: 99%